PENGARUH PROGRAM INDONESIA (PIP) TERHADAP MOTIVASI BELAJAR SISWA DI MADRASAH TSANAWIYAH MIFTAHUL ULUM CERMENAN NGORO JOMBANG - Syafi’udin; Abdul Rouf; Dian Triana (FAI- Undar, 2021)
Indonesia Pintar Program as an improvement of the Poor Students Program (BSM). Indonesia Pintar Program is a provision of cash education for children from the families who recipients of Prosperous family cards/Prosperous Family Cards (KKS), Social Protection Cards/Social Protection Cards (KPS), Family expectation Programs/Program Keluarga Harapan (PKH) or those that comply with the criteria who have been appointed from the government. The Indonesia Pintar Program is marked by the provision of a Smart Indonesia Card (KIP). Learning motivation will always be related to needs, the need for something to do, the need to please others, achieve the results, and need to overcome difficulties. With the cost of education both directly and indirectly, students have been borne by the government through the Indonesia Pintar Program so as to alleviate or reduce high school fees.The purpose of the study was to determine the effect of Indonesia Pintar Program on student learning motivation in Madrasah Tsanawiyah Miftahul Ulum Cermenan Ngoro Jombang.The object in this thesis research is students receiving assistance from Indonesia Pintar Program in Madrasah Tsanawiyah Miftahul Ulum Cermenan Ngoro Jombang, as many as 50 samples (respondents) by conducting interviews, observations and distributing questionnaires to the sample studied.Based on the results of data analysis, the final results as a conclusion in this thesis are: Indonesia Pintar Program are very significant influence on student learning motivation in Madrasah Tsanawiyah Miftahul Ulum Cermenan Ngoro Jombang.